612 Comparison of two self-expandable supra-annular bioprosthesis: a propensity score-matched analysis. (8th December 2021) - Sticchi, Alessandro; Gallo, Francesco; Marzo, Vincenzo De; Won-keun, Kim; Zeus, Tobias; Toggweiler, Stefan; Marco, Federico De; Reimers, Bernhard; Nombela-franco, Luis; Barbanti, Marco; Brugaletta, Salvatore; Piva, Tommaso; et al.
Abstract: Aims: Limited data reported the comparison of bioprostheses for transcatheter aortic valve implantation (TAVI) among devices of supra-annular design. The aim of this study is to compare the clinical outcomes of the ACURATE neo and Evolut R/PRO valves for TAVI in a propensity score-matched analysis (PSM). Methods and results: We performed a propensity score-matched analysis equalizing almost all the patient's risk factors, anatomical and procedural characteristics, and assessing the predictive value of the remaining features. Our data were derived from a large, real-world, contemporary, multicentre, international, retrospective registry of 3862 consecutive patients undergoing TAVI using two different self-expandable supra-annular valves (Medtronic Evolut R/PRO and Boston ACURATE neo). We reached a matched population of 713 couples for each device group with a medium follow-up of 456.5 days. In the comparison of the clinical outcomes between the Evolut and the ACURATE patients, no difference occurred in mortality (9.8% vs. 9.0%, P = 0.650), heart failure hospitalization (9.6% vs. 6.0%, P = 0.076), myocardial infarction (0.7% vs. 0.4%, P = 0.718), stroke (2.4% vs. 1.4%, P = 0.239), major bleeding (3.3% vs. 3.4%, P = 1.000), vascular complications (13.7% vs. 10.9%, P = 0.126), endocarditis (1.1% vs. 0.6%, P = 0.568), sepsis (0.9% vs. 0.5%, P = 0.605), acute kidney injury (0.9% vs. 0.5%, P = 0.605), and new left bundle branch block (17% vs. 13.5%, P = 0.187). The only outcome with a significant difference between the groups was the need of pacemaker implantation in favour of the ACURATE valve (5.3% vs. 12.9% for the Evolut, P < 0.001). Conclusions: In our PSM cohort, the comparison between the Evolut and the ACURATE valve showed no significant differences in the multiple outcomes evaluated, except for the rate of new pacemaker implantation. This data confirmed the recent literature, but it needs further dedicated investigation using the following devices generations.